DIFFERENCES OF STUDENTS MATHEMATIC COMMUNICATION SKILLS USING THINK PAIR SHARE COOPERATIVE LEARNING MODEL WITH NUMBERED HEAD TOGETHER - Nur Dalilah; A H Nasution; H Wardani (SEMESTA: Journal of Science Education and Teaching, 2021)
This study aims to see the differences in students' mathematical communication skills using the Think Pair Share (TPS) type of cooperative learning model with the Numbered Head Together (NHT) type. The research design was a control group pretest-posttest design. The researcher used two classes, namely experiment I and experiment II. This research was conducted at SMP N 4 Tanjung Balai, the population in this study were all students of class VIII totaling 210 people and the total sample was 60 people. As a data collection tool, namely the pretest and posttest questions where the same questions as the question 5 description. From this research it can be found that the mathematics communication skills in the class are given Think Pair Share (TPS) treatment with an average = 71,88 and Numbered Head Together (NHT) with an average = 62,16. The results of hypothesis testing with the t test where tcount > ttable is 2,789>1,671. This means that Ha is accepted, which means that there is a difference in students' mathematical communication skills in the Think Pair Share (TPS) class better than Numbered Head Together (NHT) Keywords: Mathematical Communication Skills, Think Pair Share, Numbered Head Together